Transformasi Lean Management di Industri Pertambangan: Dampaknya terhadap Kinerja Rantai Pasok dan Efisiensi Biaya Operasional - Ariyanto Wibowo; Wahyuningsih Santosa; Triwulandari Satitidjati Dewayana (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to analyze the impact of Lean Management implementation on supply chain performance and operational cost efficiency in the Indonesian mining sector. Amid increasing global pressures for efficiency and sustainability, the lean approach has become a critical strategy to eliminate waste and enhance supply chain responsiveness. A quantitative method was employed using a survey distributed to 156 respondents, including Heads of Mining Engineering, logistics managers, and relevant operational personnel. Data were analyzed using Structural Equation Modeling with the Partial Least Squares (PLS-SEM) approach. The results reveal that Lean Supply Chain Practices (LSCP) significantly mediate the relationship between Lean Management Implementation (LMI) and improvements in both supply chain performance (SCP) and operational cost efficiency (OCE). Furthermore, Organizational Readiness (OR) positively moderates the relationship between LMI and LSCP, although the effect is moderate. These findings underscore that the success of lean transformation in the mining industry heavily depends on organizational preparedness and integrated supply chain practices. These findings offer practical guidance for mining firms and contribute to the refinement of lean transformation theory in extractive supply chains.